2024
DOI: 10.1108/bij-06-2023-0416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lean-green practice and green human resource on supply chain performance: a resource-based view

Atul Kumar Sahu,
Mahak Sharma,
Rakesh Raut
et al.

Abstract: PurposeThe study examined a wide range of proactive supply chain practices to demonstrate a cross-linkage among them and to understand their effects on both practitioners of previous decision-making models, frameworks, strategies and policies. Here, six supply chain practices are empirically evaluated based on 28 constructs to investigate a comprehensive model and confirm the connections for achieving performance and competence. The study presents a conceptual model and examines the influence of many crucial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 104 publications
0
1
0
Order By: Relevance
“…Recent studies have confirmed the relevance of RBV in this field. Sahu et al [42] demonstrated that implementing lean-green practices and green human resource management has a substantial positive impact on supply chain resilience. This highlights the importance of green innovation as a crucial resource.…”
Section: Theoretical Background and Hypotheses Development 21 Underpi...mentioning
confidence: 99%
“…Recent studies have confirmed the relevance of RBV in this field. Sahu et al [42] demonstrated that implementing lean-green practices and green human resource management has a substantial positive impact on supply chain resilience. This highlights the importance of green innovation as a crucial resource.…”
Section: Theoretical Background and Hypotheses Development 21 Underpi...mentioning
confidence: 99%
“…RBV and DCT are two critical theoretical perspectives that are often used to explain how firms can achieve competitive advantage in their respective industries (Salgado et al, 2022). In SCM, RBV and DCT can be applied to help firms develop and sustain their competitive advantage over time (Sharma et al, 2023c;Sahu et al, 2024). The RBV suggests that a firm's resources and capabilities are the key determinants of its ability to achieve sustainable competitive advantage (Yoshikuni et al, 2023).…”
Section: Theoretical Backgroundmentioning
confidence: 99%